ナンキョク プリンスオラフ エンガン ノ コショウ ノ スイシツ ト EVAPORITEL ニ ツイテ - 平林, 順一; ヒラバヤシ, ジュンイチ; 小坂, 丈予; オサカ, ジョウヨ; HIRABAYASHI, Jun-ichi; OSSAKA, Joyo (国立極地研究所, 1977)
P(論文) 1972年12月から1974年2月にかけて,プリンスオラフ沿岸に点在する7つの露岩地域(新南岩,日の出岬,東オングル島,西オングル島,ラソグホブデ,スカルブスネス,スカーレン)に存在する多数の湖沼を中心とした地球化学的調査を行った.93の湖沼について湖沼水を採取し,主成分の化学分析を行い,それらの成分傾向と起源について若干の検討を行った.その結果は次の通りである.1)プリンスオラフ沿岸の湖沼は地形的に,現在も氷河が落ち込んでいるもの,海水が直接取り込まれてできたもの,窪地に融雪水などがたまってできたものなどにわけられる.2)これら湖沼水の総塩分量は6.7 mg/l～3.26×10^5 mg/lの広範囲にわたっており,ラングホブデ,スカルブスネス地域には1×10^4 mg/l以上の塩湖が多く存在しており,その他の地域では1×10^3 mg/lをこえる湖沼はほとんど認められない.3)この地域の湖沼水の成分供給源は,海水そのものと,これに加えて風送塩によるものとして考察した.また,同地域において採取したevaporiteについても粉末X線回折法により,その構成鉱物の同定を行った.これら地域におけるevaooriteは地域によって,その析出量あるいは,同定された鉱物の種類が若干異なっている.全体としてはha-lite (NaCl)を主体とし,組み合わせは異なるがthenardite (Na_2SO_4, epsomite (MgSO_4・7H_2O), hexahydrite (MgSO_4・6H_2O),gypsum (CaSO_4・2H_2O)などを含む水溶性の白色塩類が多く認められた.また,新南岩,スカーレン地域においては, atacamite (1/2(CuCl_2 ・ 3CuO ・ 3H_2O))の析出が多かった. Geochemical researches were carried out for the period from December 1972 to February 1974 on the lake waters in the following seven areas along the Prince Olav Coast; Sinnan Rocks, Gape Hinode, East Ongul Island, West Ongul Island, Langhovde, Skarvsnes and Skallen. 93 lake water samples were collected and their major components were analyzed. The following results were obtained with respect to chemical compositions of these lake waters and the origin of their salts. 1) These lakes along the Prince Olav Coast were classified into the following three types according to their topographical origin; lakes created by collapse of extant glaciers, lakes created by the direct invasion of sea water in the past, and lakes of meteoric waters in depressions of the ground. 2) Total concentration of salts in these lake waters ranges from 6.7 mg/l to 3.26×10^5 mg/l. Many high-salinity lakes where the total concentration of salts exceeds 1×10^4 mg/l were found in Langhovde and Skarvsnes, whereas in the other areas few lakes contained more than 1×10^3 mg/l salts. 3) The salts dissolved in these lake waters originate from sea water. The deviations of the chemical composition of the lake waters from that of sea water are ascribed to wind blown sea spray which ...